Implementasi Doktrin Police Power Sebagai Dasar Ekspropriasi Investor-Negara - Herlambang, Alyssa; Ruslijanto, Patricia Audrey; Ula, Hikmatul (RechtJiva, 2026)
The increasing tension between investor protection and state regulatory authority has intensified debates in international investment law, particularly concerning indirect expropriation claims in investor–state disputes. While bilateral investment treaties generally require compensation for expropriation, states frequently invoke the police power doctrine to justify regulatory measures adopted for public welfare objectives without incurring compensation obligations. However, the absence of clear normative boundaries has generated legal uncertainty in arbitral practice. This research aims to examine the criteria under which the police power doctrine may serve as a valid justification for state measures alleged to constitute expropriation, and to analyze the legal consequences arising from its application in investor–state disputes. The study employs a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials include bilateral investment treaties, UNCTAD publications, and arbitral awards. The findings demonstrate that the police power doctrine operates as a legitimate exception to compensation when state measures are enacted in good faith, pursue a genuine public purpose, are non-discriminatory, comply with due process, and satisfy proportionality requirements. When these criteria are fulfilled, regulatory actions do not amount to compensable indirect expropriation. This framework contributes to strengthening legal certainty while preserving the regulatory autonomy of states under international law.